Evaluating management zone maps for variable rate fungicide application and selective harvest - Whetton, Rebecca L.; Waine, Toby W.; Mouazen, Abdul M. (Elsevier, 2018)
Currently the majority of crop protection approaches are based on homogeneous rate fungicide application (HRFA) over the entire field area. With the increasing pressures on fungicide applications, associated with increased environmental impact and cost, an alternative approach based on variable rate fungicide application (VRFA) and selective harvest (SH) is needed. This study was undertaken to evaluate the economic viability of adopting VRSA and SH in winter wheat and the environmental benefit in terms of chemical reduction is also discussed. High resolution data of crop canopy properties, yellow rust, fusarium head blight (FHB), soil properties and yield were subjected to k-means cluster analysis to develop management zone (MZ) maps for one field in Bedfordshire, UK. Virtual cost-benefit analysis for VRFA was performed on three fungicide application timings, namely, T1 and T2 focused on yellow rust, and T3 focused on FHB. Cost-benefit analysis was also applied to SH, which assumed different selling prices between healthy and grain downgraded due to mycotoxin infection. Results showed that in this study VRFA allowed for fungicide reductions of 22.24% at T1 and T2 and 25.93% at T3 when compared to HRFA. SH reduced the risk of market rejection due to low quality and high mycotoxin content. Gross profit of combining SH and VRFA was £83.35 per hectare per year, divided into SH £48.04 ha−1, and VRFA £8.8 ha−1 for T1 and T2 and £17.7 ha−1 for T3. Total profit when considering soil and crop scanning costs would be £66.85 ha−1 per year, which is roughly equivalent to €80 or $90 ha−1 per year. This study was restricted to a single field but demonstrates the potential of fungicide reductions and economic viability of this MZ concept.
Keywords: Cereal crop disease; Management zones; Cost-benefit analysis; Selective harvest; Variable rate fungicide application